Analysis Of The Visiting Interest Of The Millenial Generation (Gen Z) To Paris Tigaras Beach, Dolok Peace District, Simalungun Regency - Mulyadi, Bejo; Gunawan, Bakti; Hutomo, Ngger Putro Cahyo (PT. Hafasy Dwi Nawasena, 2024)
This research aims to analyze the Visiting Interest of the Gen Z to Paris Beach, Simalungun Regency. The method used in this research was accidental sampling which was taken randomly. The analytical tool used is cross tabulation analysis (crosstab). From this research, it is known that of the 92 respondents who answered the questionnaire, they consisted of men (45 people), women (47 people), with the result that 57 people, both men and women, had previously come, 47 people out of a total of 92 The reason why respondents visited was because of a number of facilities, as many as 63 people said it was the first time, then the favorite activity was taking photos for 60 people, while for overnight stays 53 people said they would not stay overnight, the things they liked were the facilities for 59 people, and the response to the cleanliness of the beach area. as many as 74 people said it was clean, as many as 74 people said the service was good, the complaints found were road access to the beach. Where as many as 46 people complained about road access, and as many as 62 people said they only visited once, due to several reasons such as cost and travel time.